CHEMICAL COMPOSITION AND MEASURING THE DISTRIBUTION OF HAEMANTHIDINE BY MALDI-TOF MS IMAGING FROM Crinum scabrum LEAVES - Jennifer B. Pardo; Amanda E. Feu; Faviola A. Vigamonte; Warley de S. Borges (Química Nova)
Crinum scabrum Herb., a member of the Amaryllidaceae family, is native to Brazil and known for its diverse alkaloid content and biological potential. Previous studies identified crinamine, 6-hydroxycrinamine, and lycorine in this species. In this study, crude methanolic extracts from leaves and bulbs were prepared, followed by alkaloid enrichment via acid-base extraction. Electrospray ionization-linear trap quadrupole-cross-linking tandem mass spectrometry (ESI-LTQ-XL-MS/MS) analysis annotated crinamine, lycorine, and haemanthidine/6-epi-haemanthidine. Further separation using silica gel column chromatography and 1H nuclear magnetic resonance (NMR) analysis revealed the epimers mixture of haemanthidine/6-epi-haemanthidine (C1/2), crinamine (C3), and trisphaeridine (C4). Due to the high yield of C1/2 (24.4%), matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) analysis was performed on the leaves, showing widespread distribution of ion peaks (m/z 318.144) corresponding to C1/2. These results underscore the significance of haemanthidine and its epimer, suggesting that Crinum scabrum leaves are a promising source of these alkaloids and facilitate further investigation of its potential biological activities.